Game theoretic modeling of NGANs: impact of retail and wholesale services price variation - Pereira, João Paulo (2013)
The increasing demand for broadband access leads operators to upgrade the existing access infrastructures (or building new access network). Broadband access networks require higher investments (especially passive infrastructures such as trenches/ducts and base station towers/masts), and before making any decision it is important to analyze all solutions. The selection of the best solution requires understanding the technical possibilities and limitations of the different access technologies, as well as understanding the costs of building and operating the networks. This study analyzes the effect of asymmetric retail and wholesale prices on operators’ NPV, profit, consumer surplus, welfare, retail market, wholesale market, and so on. For that, we propose a tehno-economic model complemented by a theoretic-game model. This tool identifies all the essential costs of building (and operating) access networks, and performs a detailed analysis and comparison of the different solutions in various scenarios. Communities, operators/service providers, and regulators can use this tool to compare different technological solutions, forecast deployment costs, compare diferente scenarios, and so on, and help them in making deployment (or regulatory) decisions. The game-theory analyses give a better understanding of the competition and its effect on the business case scenarios’ economic results.